2023
DOI: 10.2196/40961
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Patient Uptake of and Engagement With the National Health Service Digital Diabetes Prevention Programme: Qualitative Interview Study

Abstract: Background Digital diabetes prevention programs (digital-DPPs) are being implemented as population-based approaches to type 2 diabetes mellitus prevention in several countries to address problems with the uptake of traditional face-to-face diabetes prevention programs. However, assessments of digital-DPPs have largely focused on clinical outcomes and usability among those who have taken them up, whereas crucial information on decision-making about uptake (eg, whether a user downloads and registers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Additionally, access to peer support was associated with a significantly greater weight reduction at 12 months in a recent evaluation of the pilot NHS-DDPP ( Ross et al, 2022 ). On the other hand, people on the NHS-DDPP report to opt for digital programmes because they do not like the group aspect ( Ross et al, 2023 ), and these larger online networks (akin to social media) may lack the ‘critical mass’ to deliver sufficient personalised support ( Elaheebocus et al, 2018 ). This may explain why users on the provider programme who offered closed peer group support moderated by a health coach showed higher engagement with this intervention feature in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, access to peer support was associated with a significantly greater weight reduction at 12 months in a recent evaluation of the pilot NHS-DDPP ( Ross et al, 2022 ). On the other hand, people on the NHS-DDPP report to opt for digital programmes because they do not like the group aspect ( Ross et al, 2023 ), and these larger online networks (akin to social media) may lack the ‘critical mass’ to deliver sufficient personalised support ( Elaheebocus et al, 2018 ). This may explain why users on the provider programme who offered closed peer group support moderated by a health coach showed higher engagement with this intervention feature in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] We also explored decisions about taking up the digital offer and found that these were based on similar issues to the conventional format (such as self-efficacy) as well as unique features of the digital interventions such as enhanced accessibility. 42 We also found that professional support remained important even with digital delivery. 41…”
Section: Digital Nhs Dppmentioning
confidence: 65%
“…IMPROVING UPTAKE 1. Communication with patients 24,25,42 Around 50% of those referred take up a place on the NHS DPP. Around 30% of patients do not recall being invited.…”
Section: Findings Actionable Insightsmentioning
confidence: 99%
“…This finding accords with previous research. 28 Some participants also attributed this level of disengagement to not being able to relate to the other users posting on the forums, a similar barrier to some participants’ engagement with the group chats offered by Provider 1. Notably, some participants supported the principle of discussion forums, acknowledging their role in facilitating idea sharing and supporting behavioural changes, but chose not to engage as it did not align with participants’ own perceptions of how they preferred to communicate with others: I just don’t do social media.…”
Section: Resultsmentioning
confidence: 99%